Low CD4⁺/CD25⁺/CD127⁻ regulatory T cell- and high INF-γ levels are associated with improved survival of neuroblastoma patients treated with long-term infusion of ch14.18/CHO combined with interleukin-2. (2nd December 2019) - Troschke-Meurer, Sascha; Siebert, Nikolai; Marx, Madlen; Zumpe, Maxi; Ehlert, Karoline; Mutschlechner, Oliver; Loibner, Hans; Ladenstein, Ruth; Lode, Holger N.
ABSTRACT: Immunotherapy with the anti-GD2 antibody (Ab) ch14.18/CHO in combination with interleukin 2 (IL-2) has improved survival of high-risk neuroblastoma (NB) patients. Here, we report immunotherapy-related effects on circulating NK cells, regulatory T cells (Tregs ), granulocytes as well as on Ab-dependent cell-mediated cytotoxicity (ADCC) and cytokines IFN-γ, IL-6, IL-10, IL-18 and CCL2 and their association with progression-free survival (PFS). In a closed single-center program, 53 patients received five cycles of 6 × 10 6 IU/m 2 subcutaneous IL-2 (d1-5; 8–12) combined with long-term infusion (LTI) of 100 mg/m 2 ch14.18/CHO (d8-18). Immune cells and cytokines were analyzed by flow cytometry and ADCC by calcein-AM-based cytotoxicity assay. IL-2 administration increased cytotoxic NK cell-, eosinophil- and Treg counts in cycle 1 (2.9-, 3.1- and 20.7-fold, respectively) followed by further increase in subsequent cycles, whereas neutrophil levels were elevated only after the ch14.18/CHO infusion (2.4-fold change). Serum concentrations of IFN-γ, IL-6, IL-10, IL-18 and CCL2 in cycle 1 were increased during the combinatorial therapy (peak levels of 3, 656 ± 655 pg/ml, 162 ± 38 pg/ml, 20.91 ± 4.74 pg/ml, 1, 584 ± 196 pg/ml and 2, 159 ± 252 pg/ml, respectively). Surprisingly, we did not observe any correlation between NK-, eosinophil- or neutrophil levels and PFS. In contrast, patients with low Tregs showed significantly improved PFS compared to those who had high levels. Treg counts negatively correlated with INF-γ serum concentrations and patients with high INF-γ and IL-18 had significantly improved survival compared to those with low levels. In conclusion, LTI of ch14.18/CHO in combination with IL-2 resulted in Treg induction that inversely correlated with IFN-γ levels and PFS.